Internalisasi Nilai-Nilai Moderasi Beragama dalam Pendidikan Karakter di Sekolah Dasar - Umah, Restu Yulia Hidayatul; Werdiningsih, Wilis; Anggraini, Yulia (Proceedings of Annual Conference for Muslim Scholars, 2022)
Elementary school age is an age that is vulnerable to deviant behavior. Things that are considered fun will continue to be done even though it is deviant behavior. For example, the frequency of seeing "prank" content, "greetings from binjai", and so on is considered normal, funny, and fun, then happily practicing it with friends without realizing it can hurt other people. If excessive or extreme behavior continues to occur in elementary school-age children, it is feared that radicalism will become ingrained when they grow up. So efforts to prevent radicalism from elementary school age can be internalized in character education such as religious, nationalism, mutual cooperation, independence, and integrity. The purpose of this study is to internalize the values ​​of religious moderation in elementary schools through character education. This research is qualitative research with a descriptive analysis type. The results of the analysis show that the values ​​of religious moderation can be integrated into character education in elementary schools by using indirect learning, where every student learning is accustomed to superior characters and moderate noble character. Keywords: